2011
DOI: 10.7589/0090-3558-47.3.501
|View full text |Cite
|
Sign up to set email alerts
|

DNA VACCINATION OF BISON TO BRUCELLAR ANTIGENS ELICITS ELEVATED ANTIBODY AND IFN-γ RESPONSES

Abstract: ABSTRACT:Brucella abortus remains a threat to the health and well-being of livestock in states bordering the Greater Yellowstone Area. During the past several years, cohabitation of infected wildlife with cattle has jeopardized the brucellosis-free status of Idaho, USA; Wyoming, USA; and Montana, USA. Current livestock B. abortus vaccines have not proven to be efficacious in bison (Bison bison) or elk (Cervus elaphus nelsoni). One problem with the lack of vaccine efficacy may stem from the failure to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…1 inducing not only high IgG1 titers but also cellular response of IFN-γ, IL-4, IL-5 and IL-6 [11][13]. In a separate study, we determined the IFN-γ response specific to T cell epitopes of BP26 in sheep ( data not shown ), which also indicated that BP26 was responsible for the mixed Th cell response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 inducing not only high IgG1 titers but also cellular response of IFN-γ, IL-4, IL-5 and IL-6 [11][13]. In a separate study, we determined the IFN-γ response specific to T cell epitopes of BP26 in sheep ( data not shown ), which also indicated that BP26 was responsible for the mixed Th cell response.…”
Section: Discussionmentioning
confidence: 99%
“…The 62% (18/29) IgG1 of murine mAbs obtained in the present study, it suggested that BP26 might be associated with Th2 cytokine responses. Additionally the presence of BP26 enhanced antibody response to the chaperone protein, trigger factor (TF) [11][13], suggested that BP26 and other relevant proteins such as TF and omp31 might be involved in protective immunity to Brucella infections [25]–[28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using B. abortus soluble antigens combined with the adjuvant of dimethyldioctadecyl ammonium bromide to immunize steers, both humoral and cell-mediated immune responses were elicited (Dzata et al, 1991). Bison immunized intramuscularly with Bp26 and TF DNA vaccines produced enhanced antibody, proliferative T cell, and IFN-γ responses, indicating elicited cellular immune responses (Clapp et al, 2011b). Future studies are needed to assess the efficacy of this approach in livestock.…”
Section: Subunit Brucella Vaccinesmentioning
confidence: 99%
“…The reproductive cycle of female wood bison is well described, leading to techniques for successful embryo transfer and manipulation of the reproductive cycle to allow superovulation and artificial insemination (McCorkell 2008Adams et al 2010;Palomino et al 2010Palomino et al , 2011Palomino et al , 2012 (Lima et al 2003;Pan et al 2003;Nor and Musa 2004;Rhee et al 2004;Luo et al 2006a, b;Li et al 2008;Mir et al 2009;Silva et al 2009;Lee et al 2010), cattle, and bison (Clapp et al 2011). Combined bTB and brucellosis vaccines are more efficacious than either vaccine component alone in cattle (Hu et al 2009a(Hu et al , b, 2010.…”
Section: Genetic Salvage Optionsmentioning
confidence: 99%